Fig. 58 in Coccolithophorids in Polar Waters: Pappomonas spp. Revisited ... - Thomsen, Helge A.; Østergaard, Jette B. (Zenodo, 2014)
Fig. 58. Interpretation of rim calcification (body coccoliths) in species of Pappomonas and Papposphaera. A – Pappomonas flabellifera (NEW / micrograph 25036); B – Pappomonas borealis (NEW / micrograph 24879); C – Pappomonas weddellensis (ANT X/3 / micrograph 20549); D – Pappomonas garrisonii sp.nov. (ANT X/3 / micrograph 21149); E – Papposphaera sagittifera (NEW / micrograph 24930); F–G – Balaniger virgulosa HET scale rim (F) and base plate calcification (G) (West Greenland / micrograph 10322). ... : Published as part of Thomsen, Helge A. & Østergaard, Jette B., 2014, Coccolithophorids in Polar Waters: Pappomonas spp. Revisited, pp. 235-256 in Acta Protozoologica 53 (3) on page 253, DOI: 10.4467/16890027AP.14.022.1997, http://zenodo.org/record/12638350 ...